2012
DOI: 10.1177/0091270010391790
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylcysteine as a Novel Prophylactic Treatment for Ifosfamide‐Induced Nephrotoxicity in Children: Translational Pharmacokinetics

Abstract: Ifosfamide (IFO), which is used in the treatment of pediatric solid tumors, causes high rates of nephrotoxicity. N-acetylcysteine (NAC), an antidote for acetaminophen overdose, has been shown to prevent IFO-induced renal cell death and nephrotoxicity in both LLCPK-1 cells and a rat model. To facilitate the use of NAC in preventing IFO-induced nephrotoxicity in children, the authors compared the systemic exposure to NAC in children treated for acetaminophen overdose to the systemic exposure of the therapeutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Similarly, younger age has been identified as 1 of the major risk factors for valproic acid–induced hepatotoxicity . A similar pattern has been demonstrated for ifosfamide, in that young children are at increased risk for ifosfamide‐induced nephrotoxicity that we believe to be due to increased ability to produce the toxin chloroacetaldehyde by side‐chain oxidation of ifosfamide versus oxidative metabolism of ifosfamide to isophosphoramide mustard, the desired antitumor metabolite . When contemplating therapy for toddlers and early school age children—notably in the context of complex chronic care—ADR risk needs to be factored into care planning.…”
Section: The Ontogeny Of Adverse Drug Reactionssupporting
confidence: 55%
See 1 more Smart Citation
“…Similarly, younger age has been identified as 1 of the major risk factors for valproic acid–induced hepatotoxicity . A similar pattern has been demonstrated for ifosfamide, in that young children are at increased risk for ifosfamide‐induced nephrotoxicity that we believe to be due to increased ability to produce the toxin chloroacetaldehyde by side‐chain oxidation of ifosfamide versus oxidative metabolism of ifosfamide to isophosphoramide mustard, the desired antitumor metabolite . When contemplating therapy for toddlers and early school age children—notably in the context of complex chronic care—ADR risk needs to be factored into care planning.…”
Section: The Ontogeny Of Adverse Drug Reactionssupporting
confidence: 55%
“…53,54 A similar pattern has been demonstrated for ifosfamide, in that young children are at increased risk for ifosfamideinduced nephrotoxicity that we believe to be due to increased ability to produce the toxin chloroacetaldehyde by side-chain oxidation of ifosfamide versus oxidative metabolism of ifosfamide to isophosphoramide mustard, the desired antitumor metabolite. 55 When contemplating therapy for toddlers and early school age children-notably in the context of complex chronic care-ADR risk needs to be factored into care planning. A potentially important and largely unexplored consideration germane to ontogeny is the potential impact of developmental changes in receptor and transporter expression and activity on risk for ADRs.…”
Section: S41mentioning
confidence: 99%
“…At overdoses, however, APAP leads to accumulation of NAPQI 1 and critical depletion of GSH. 3 The mechanism of APAP-induced nephrotoxicity is not entirely known. It is thought to be due to oxidative stress with a critical depletion of GSH and renal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Early in vitro and in vivo animal studies have shown the effectiveness of NAC in preventing IFO toxicity, as well its lack of interference on the antineoplastic effects of IFO. These findings have been supported by three clinical experiences , although randomized controlled trials (RCTs) are required to assess the role NAC played in protection of the kidney in the published cases. Given the promise of anti‐oxidants, and in particular NAC, further research needs to be carried out to determine which potential treatments are the most clinically useful.…”
Section: Cancer Chemotherapeuticsmentioning
confidence: 80%